[A Note on a Point in Value and Capital]: A Rejoinder - Morishima, M. (Review of Economic Studies, 1953)
Journal Article A Rejoinder Get access M. Morishima M. Morishima Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Page 222, https://doi.org/10.2307/2295776 Published: 01 January 1953